Evaluation of the Playgroup Project and Alternative Learning System Programs In Village Looc and Village Opao, Mandaue City, Cebu, Philippines - Ruiz, Glenlie; Pilapil, Gina Fe; Rule, Katrina Jan Alexa; Tulod, Stephanie Anne (JPAIR Institutional Research, 2019)
The College of Teacher Education responds to the needs of its partner communities in Mandaue City, Cebu, Philippines as it implements the Playgroup Project and the Alternative Learning System (ALS) Programs. The college has integrated its community extension programs into the academic and extra-curricular activities of the students. Student-teachers render extension services to Village Looc and Village Opao. The university funds these programs, which are supported by the faculty and other stakeholders. This descriptive, qualitative study evaluated the implementation of the two community extension programs among its beneficiaries. In the Playgroup Project, parents are satisfied with the implementation of the program. They believe that the project yields favorable results and would benefit more families in the community. The program, implemented by the faculty, students, non-teaching staff, and alumni volunteers, utilizes the resources and facilities of the university. Based on the parents’ testimonies, there is a strong association between the participation of their children in the program, their learning competence, and their social and emotional well-being. The program has increased the readiness of the learners for a smooth transition to kindergarten. The improvement of the learners’ dependability level had helped the parents ease their concern for their children’s safety. On the other hand, the ALS Program, in cooperation with DepEd Mandaue City, involved the student-teachers and volunteers in the mapping of potential ALS learners, learning sessions, and culminating activities. This study revealed that the ALS Program had touched lives across different socio-economic backgrounds.